Intimate partner violence among Nepalese women and associated factors in 2021-2022. - Masood Ali Shaikh (PLOS Global Public Health)
Intimate partner violence (IPV) remains a significant public health challenge globally, impacting millions and contributing to preventable suffering and pain, both emotionally and physically. In Nepal, like many other nations, tackling IPV is a key priority on the path to achieving sustainable development goals. IPV prevalence and its correlates were studied using the deidentified data for secondary analysis from the 2022 Nepal Demographic and Health Survey (DHS), and changes in IPV at the urban, rural, and national levels from the 2016 Nepal DHS. These cross-sectional surveys employed a two-stage cluster sampling technique. In the Nepal DHS 2022, a total of 4,523 ever-partnered women were included and administered IPV-related questions. Various socio-demographic, attitudinal, and experiential attributes of 15-49 year old women were identified and used in the simple and multiple logistic regression models for computing the bivariate and multivariable associations with IPV. Over their lifetime, 27.27% women experienced IPV perpetrated by their current or most recent husband/intimate partner, with physical IPV being the most common type reported. The six statistically significant factors associated with IPV in the multivariable model included educational level of women and their partner, number of living children, use of alcohol by partner, knowing about father having ever beaten mother, and controlling behavior displayed by partner. While changes in IPV from 2016 to 2022 were not statistically significant. One in four women having experienced IPV in their lifetime in Nepal with no discernable change over the course of 6-years is a major public health challenge requiring investing in programs that encourage and ensure economic and social autonomy for women and change in the harmful gender norms.